Recent progress of sol-gel coating of pure magnesium in biomedical applications. A review - Aufa, A. N. (Universiti Putra Malaysia Press, 2021)
Magnesium (Mg) has attracted great attention as a possible biomedical implant due to its appropriate mechanical property, good biocompatibility, and lightweight. However, fast and uneven degradation has been a significant problem of pure Mg. The goal of this review was to investigate the current state of the art in the corrosion resistance and load-bearing capacities of osteopromotive biomaterials created by altering Mg surface coating with Hydroxyapatite (HA) ceramics. Initially, the osteopromotive characteristics of magnesium and also the magnesium corrosion behaviour in the human body’s microenvironment were discussed. Following that, the different HA sol-gel coating methods in modifying the surface and corrosion behaviour of Mg were established. It was proposed that the optimal HA coating is about 5 to 6 µm as a corrosion barrier, which may also be improved by heat treatment at temperatures ranging from 300°C to 450°C. Finally, the strategies of HA sol-gel surface modification to improve the apatite formed and their degradation issue to promote healing in orthopaedic high load-bearing skeletal sites were elucidated.